Sculpteremaeus olszanowskii gen. nov., sp. nov. (Acari, Oribatida, Cymbaeremaeidae) from chaparral in California, USA, with a reassessment of Cymbaeremaeidae - Behan-Pelletier, Valerie M.; Ermilov, Sergey G. (Zootaxa, 2020)
A new oribatid mite genus, Sculpteremaeus gen. nov. (Oribatida, Cymbaeremaeidae), with Sculpteremaeus olszanowskii sp. nov. as type species, is proposed and described based on adults. It is from sandy soil-litter in chaparral of California, USA, an environment from which no oribatid mites have been recorded previously. Based on an analysis of adults of all genera of Cymbaeremaeidae, the new genus is closely related to Ametroproctus, from which it is most easily distinguished by the morphology of lamellae, size of lamellar cusps, and shape of the tutorium. We expand the Cymbaeremaeidae family diagnosis, and question the inclusion of Scapheremaeus based on extensive molecular evidence showing its closer relationship with Ameronothroidea and Licneremaeoidea.